1998
DOI: 10.1046/j.1365-2133.1998.02233.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ulcerative keratitis associated with erythema elevatum diutinum and a positive rheumatoid factor: a report of three cases

Abstract: Peripheral ulcerative keratitis (PUK) is a complication of collagen-vascular diseases such as rheumatoid arthritis (RA) and other systemic vasculitides. We report three cases of erythema elevatum diutinum with PUK. These patients presented with nodules and plaques consistent with erythema elevatum diutinum on the extremities and crusted or ulcerated purpuric lesions on the soles. Histopathological examination of these lesions revealed a dense neutrophilic infiltrate with nuclear dust and fibrin around blood ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 13 publications
0
23
1
1
Order By: Relevance
“…4 Cases of EED associated with PUK are rare, with very few described in the literature. 1,5,6 Herein, we report on a case with biopsyproven EED associated with PUK, which, unlike previously reported cases, coexisted with RA and positive rheumatoid factor.…”
Section: Have Been Reportedcontrasting
confidence: 52%
“…4 Cases of EED associated with PUK are rare, with very few described in the literature. 1,5,6 Herein, we report on a case with biopsyproven EED associated with PUK, which, unlike previously reported cases, coexisted with RA and positive rheumatoid factor.…”
Section: Have Been Reportedcontrasting
confidence: 52%
“…Rheumatoid vasculitis from systemic arteritis to mild cutaneous vasculitic lesions 5 and related diseases, such as pyoderma gangrenosum and erythema elevatum diutinum, are also well recognized to be associated with RA. 6,7 We encountered 4 patients with RA at 3 different hospitals who had developed irregular erythematous patches over and around the elbow joints. These patients showed a similar clinical appearance and specific histopathologic findings, ie, histiocytic aggregates in markedly dilated blood or lymph vessels in the dermis.…”
mentioning
confidence: 98%
“…Hernandez-Cano et al reported the disappearance of EED lesions in a patient with a liver transplantation following a reduction in cyclosporin dosage [12]. However, EED lesions may not respond to dapsone, or if they do, recurrences are quite common [5,11,24,31,39]. It is possible that the marked fibrosis in late lesions may account for the lack of response to dapsone [8].…”
Section: Discussionmentioning
confidence: 90%
“…Other conditions reported to be associated include hyperimmunoglobulinemia D syndrome, cryoglobulinemia, myelodysplastic syndromes, abnormalities in the clotting mechanism, haematological malignancies, prostatic carcinoma, testicular lymphoma, viral and bacterial infections, rheumatic fever, HIV infection, inflammatory bowel disease, rheumatoid arthritis and peripheral ulcerative keratitis, relapsing polychondritis, Wegener's granulomatosis, and acro-osteolysis [1,9,10,16,18,23,24,37,39,40,41,42].…”
Section: Discussionmentioning
confidence: 96%